Fundraising on the fringe: Do ideologically extreme candidates solicit small donations? - Seo-young Silvia Kim (Research & Politics)
Do ideologically extreme candidates actively pursue small donations? The literature on money in politics debates whether “small” individual campaign donors are more ideologically extreme than large donors. This paper reverses the question, investigating whether extreme candidates request smaller contributions from potential donors. Using data from U.S. congressional candidates’ fundraising platforms in the 2020 elections, I examine how campaigns typically present a set of suggested donation amounts to solicit money from potential donors efficiently. While party, in-state income levels, and the usage of major fundraising platforms mattered, ideological extremism had no bearing on the amounts candidates asked for. Given that solicitation amounts have been long and easily optimized through A/B testing, I interpret this as extreme candidates not finding it profitable to ask for smaller amounts, which is more aligned with the view that small donors are not more ideologically extreme than large donors.